Desenvolvimento de fécula de mandioca auto-expansível - Demiate, Ivo Mottin [UNESP] (Universidade Estadual Paulista (Unesp), 1999)
A produção de fécula de mandioca fermentada e seca ao sol (polvilho azedo) em alguns países da América do Sul, citada na literatura, é um exemplo de geração da propriedade funcional denominada auto-expansão. O polvilho azedo é empregado na elaboração de produtos alimentícios em caráter comercial. Estudos da propriedade de expansão do polvilho azedo possibilitaram concluir que a exposição de fécula de mandioca tratada com ácido lático a radiação ultravioleta (UV)* é capaz de promover o aparecimento dessa propriedade. No presente trabalho propõe-se o desenvolvimento de féculas de mandioca auto-expansíveis modificadas por processo químico simplificado se comparado à obtenção do polvilho azedo ou da fécula tratada com ácido lático e irradiada com UV. Esse processo consta da oxidação da fécula de mandioca com solução de permanganato de potássio e posterior suspensão dessa fécula em solução de ácido lático. As amostras secas em estufa são lavadas para remoção do excesso de reagentes. As lavagens não...

The production of fermented and sundried cassava starch (cassava sour starch) in some countries of South America, as described in the literature, is an example of generation of the functional property denominated expansion ability (auto-expansion). In Brazil, this fermented starch is commercially employed in the production of several food products. Studies about physico-chemical characteristics of cassava sour starch indicated that UV-irradiation of lactic acid treated cassava starch* generated modified starches that expanded just as cassava sour starch. In the present work the development of chemically modified cassava starch is proposed by a chemical process less complex than that employed on the production of cassava starches presenting expansion ability (cassava sour starch or UV-irradiated lactic acid treated cassava starch). This process involves previous oxidation of native cassava starch with potassium permanganate, followed by suspension in lactic acid solution. The samples are oven-dried before or after being washed to promote the removal of excess reagents. Washings do not influence the expansion of the modified samples. Oxidized starches described in the literature form clear and low viscosity pastes and are used mainly at the textile and paper industry. Their expansion property, however, was never... (Complete abstract click electronic access below)
Keywords: Acido latico; Fécula de mandioca; Lactic acid